Business studies. Grade 11 - De Nobrega, C; C. De Nobrega (Pietermaritzburg: Shuter & Shooter, 2017)
Business studies grade 11 concepts are simplified for easier learning. Examiners often comment on learners' lack of content knowledge, and how this impacts their ability to write well-structured and intelligent essays.
Keywords: Business education Problems, exercises, etc